Molecular detection of P. vivax and P. ovale foci of infection in asymptomatic and symptomatic children in Northern Namibia. - Daniel H Haiyambo; Petrina Uusiku; Davies Mumbengegwi; Jeff M Pernica; Ronnie Bock; Benoit Malleret; Laurent Rénia; Beatrice Greco; Isaac K Quaye (Public Library of Science (PLoS), 2019)
Background Knowledge of the foci of Plasmodium species infections is critical for a country with an elimination agenda. Namibia is targeting malaria elimination by 2020. To support decision making regarding targeted intervention, we examined for the first time, the foci of Plasmodium species infections and regional prevalence in northern Namibia, using nested and quantitative polymerase chain reaction (PCR) methods. Methods We used cross-sectional multi-staged sampling to select 952 children below 9 years old from schools and clinics in seven districts in northern Namibia, to assess the presence of Plasmodium species. Results The median participant age was 6 years (25-75%ile 4-8 y). Participants had a median hemoglobin of 12.0 g/dL (25-75%ile 11.1-12.7 g/dL), although 21% of the cohort was anemic, with anemia being severer in the younger population (p<0.002). Most of children with Plasmodium infection were asymptomatic (63.4%), presenting a challenge for elimination. The respective parasite prevalence for Plasmodium falciparum (Pf), Plasmodium vivax (Pv) and Plasmodium ovale curtisi (Po) were (4.41%, 0.84% and 0.31%); with Kavango East and West (10.4%, 6.19%) and Ohangwena (4.5%) having the most prevalence. Pv was localized in Ohangwena, Omusati and Oshana, while Po was found in Kavango. All children with Pv/Pf coinfections in Ohangwena, had previously visited Angola, affirming that perennial migrations are risks for importation of Plasmodium species. The mean hemoglobin was lower in those with Plasmodium infection compared to those without (0.96 g/dL less, 95%CI 0.40-1.52 g/dL less, p = 0.0009) indicating that quasi-endemicity exists in the low transmission setting. Conclusions We conclude that Pv and Po species are present in northern Namibia. Additionally, the higher number of asymptomatic infections present challenges to the efforts at elimination for the country. Careful planning, coordination with neighboring Angola and execution of targeted active intervention, will be required for a successful elimination agenda.